Bhadra Wildlife Sanctuary-a Fragile Ecosystem - Raju, R.; Heggde, S. N. (Indian Forester, 1995)
Nature has endowed India with a magnificent asset in its rich and varied wildlife. It is estimated that there are over 500 species of mammals in the country. In bird population India possesses one of the richest avifauna in the world. Wildlife, an important constituent of natural biotic complex, could exist in a natural state of equilibrium with its environment, governed by the laws of natural selection if there is no human interference. Man however has been persecuting wildlife for his demands without appreciating its importance in maintaining the equilibrium of dynamic nature. As a result of this folly several species of animals and birds have become either extinct or are threatened with extinction.